Penghilangan Penurunan Kadar Phenol Pada Air Limbah Dengan Menggunakan Enzim Peroksidase Dan Koagulan - Aida Soelaeman (Jurnal Kimia dan Kemasan, 1995)
Phenols are effectively removed by treatment with peroxidase and a cationic polymer coagulant. The coagulant precipitated enzymatic products of phenol, and reduced the in activation of peroxidase caused by reaction of products from phenol with the enzyme.